331PA retrospective analysis of immune checkpoint therapy in patients with non-small cell lung cancer: Focus on thyroid disorder. (24th November 2019) - Ono, S; Senju, H; Taniguchi, H; Tomono, H; Shimada, M; Hayashi, F; Suyama, T; Honda, N; Umeyama, Y; Dotsu, Y; Gyotoku, H; Takemoto, S; et al.
Abstract: Background: Previous reports suggested that development of an immune-related adverse event (irAE), including thyroid disorder (TD), is associated with better outcomes of immune checkpoint inhibitor (ICI) therapy. Though TD has been reported most frequently as an irAE, it has not been well analyzed compared to life-threatening adverse events such as interstitial lung disease or colitis. Methods: We conducted a chart-based retrospective analysis of patients (Pts) with advanced or recurrent non-small cell lung cancer (NSCLC), who are treated with monotherapy using nivolumab, pembrolizumab, or atezolizumab between January 2016 and June 2019 in two facilities in Japan. TD emerging after the first treatment with an ICI was considered as an irAE. Tumor response was evaluated with Response Evaluation Criteria in Solid Tumors version 1.1. Progression-free survival (PFS) and overall survival (OS) on ICIs were evaluated with Kaplan-Meier method. The correlations between time to onset of TD and PFS or OS were analyzed with Spearman's rank correlation coefficient. Results: In total, 164 consecutive Pts were enrolled. The median age was 68 (range: 34-84) years, and 40 (24.4%) were women. TD of any grade occurred in 26 Pts (15.8%); 11/15/0/0/0 cases were classified as Grade 1/2/3/4/5, respectively, according to Common Terminology Criteria for Adverse Events version 5.0. Onset of TD ranged from 6 to 455 (median: 77.5) days after the first treatment with an ICI. Objective response rates in Pts with and without TD were 28.0% and 18.1%; disease control rates were 68.0% and 50.7%, respectively. Median PFS and OS were significantly longer in Pts with TD (PFS: 226 vs 100 days, p = 0.029; OS: not reached vs 434 days, p = 0.050, log-rank test). Among TD Pts, however, a positive correlation between time to onset of TD and PFS was identified (p = 0.0015). Significantly shorter PFS was observed in Pts with earlier TD onset, especially within 30 days, compared to Pts with later TD onset (median PFS: 72.5 vs 329 days, p = 0.00096, log-rank test). Conclusions: Development of TD caused by ICIs was associated with longer PFS. Nevertheless, the prognosis of Pts with early onset of TD was poor. This study suggested that physicians should consider the onset of TD in Pts using ICIs. Legal entity responsible for the study: Hiroyuki Yamaguchi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.